The pivotal role of sleep in mediating the effects of life stressors and healthy habits on allostatic load in mid-life adults - Buller-Peralta, Ingrid; Gregory, Sarah; Low, Audrey; Dounavi, Maria-Eleni; Bridgeman, Katie; Ntailianis, Georgios; Lawlor, Brian; Naci, Lorina; Koychev, Ivan; Malhotra, Paresh; O'Brien, John T.; Ritchie, Craig W.; et al. (Frontiers in Human Neuroscience, 2024)
ObjectivesWe assessed the modulation of allostatic load (AL) by engagement in healthy habits and life stressors, mediated through resilience and the perceived influence of the stressors. Sleep was included as third mediator given extensive evidence associating to all the analysed factors.MethodsStructural equation models to assess the modulation of AL by either traumatic or psychosocial stressors and healthy habits were generated with data from 620 mid-life adults (age 51.3 ± 5.48 years). Model 1 included self-reported life stressors, engagement in cognitive and physical activities, resilience and a pyramid score for diet. In Model 2, self-reported sleep quality was included in the mediation analysis between resilience and perceived stress on AL.ResultsDirect effects of sports and diet on AL, and on resilience by sports were found in all the evaluated models. The modulation of AL by both types of stressors was only revealed in model 2, through indirect effects of perceived influence via sleep quality. An effect of sport habits on AL via resilience was found to be mediated by sleep, and equivalent but opposed effects of perceived influence of stressors and resilience on sleep quality emerged as critical factor for AL modulation.ConclusionOur results suggest that sleep plays a pivotal role in the modulation of AL by both life stressors and sport habits, balancing the harmful and protective effects of perceived stress and resilience. The relative weight of one over the other to worsen or improve sleep quality will determine the resulting level of AL.